Pengaruh Modernisasi Terhadap Eksistensi Permainan Tradisional di Gempuran Permainan Modern Bagi Mahasiswa Teknik Lingkungan 2022 - Alifia Putri; Alodisa Putri; Drestanala Hapsari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Modernization is a bridge for humans to start a new era. The digital world which is growing rapidly brings many changes in various aspects and joints of the wider community's life. One of the aspects affected by modernization is the existence of traditional games. Traditional games as we already know are the nation's cultural heritage which has become a culture in Indonesian society. Traditional games are also the nation's cultural wealth. In this research, we aim to review the knowledge of the younger generation, namely UPN